2020
DOI: 10.1371/journal.pone.0232746
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the ocean as a source for atmospheric microplastics

Abstract: Global plastic litter pollution has been increasing alongside demand since plastic products gained commercial popularity in the 1930's. Current plastic pollutant research has generally assumed that once plastics enter the ocean they are there to stay, retained permanently within the ocean currents, biota or sediment until eventual deposition on the sea floor or become washed up onto the beach. In contrast to this, we suggest it appears that some plastic particles could be leaving the sea and entering the atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(195 citation statements)
references
References 63 publications
3
152
3
4
Order By: Relevance
“…Many of these models use a "typical", "widemarine", or "narrow-continental" size distribution that does not account for the natural variability in aerosol size distributions or reflect their complexity. Additionally, with the mounting evidence of microplastic particles, with sizes between 4-188 µm, present in the atmosphere and in rain (Allen et al, 2020;Brahney et al, 2020), it is of greater importance to include and further study the impact of particles with D p > 10 µm on cloud and precipitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these models use a "typical", "widemarine", or "narrow-continental" size distribution that does not account for the natural variability in aerosol size distributions or reflect their complexity. Additionally, with the mounting evidence of microplastic particles, with sizes between 4-188 µm, present in the atmosphere and in rain (Allen et al, 2020;Brahney et al, 2020), it is of greater importance to include and further study the impact of particles with D p > 10 µm on cloud and precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Aerosols influence cloud processes by serving as cloud condensation nuclei (CCN) on which cloud droplets can form (Köhler, 1936). The size of CCN determines the droplets' initial size distribution and hence impacts cloud processes and properties, such as size (Rosenfeld et al, 2008;Altaratz et al, 2014;Koren et al, 2014), lifetime (Albrecht, 1989), optical properties (Twomey and Squires, 1959;Twomey, 1977;Mülmenstädt and Feingold, 2018), and rain amounts and patterns (Yin et al, 2000b;Rosenfeld et al, 2006;Xue et al, 2008;Yuan, 2011;Altaratz et al, 2014;Koren et al, 2014;Seigel, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Along with plastic waste, disposable masks can reach land and aquatic systems, where animals may become entangled or eat them by mistake ( Sigler, 2014 ; Vegter et al, 2014 ). Recent evidence has shown that microplastics can reach remote regions of the planet, and also end up in our bodies through food intake and breathing ( Allen et al, 2020 ).…”
Section: Indirect Impact Of Covid-19 On the Environmentmentioning
confidence: 99%
“…The atmosphere is thus clearly a transport pathway for microplastics to reach the ocean. Recent work also suggests that the atmosphere may also be a pathway for microplastics to exit the ocean via bubble burst ejection and wave action (Allen et al, 2020). As such, mass balance estimates must consider atmospheric transport as pathways both into and out of the ocean.…”
Section: The Fate Of Plastic In Our Oceanmentioning
confidence: 99%